SUSTAINABLE CULTURAL TOURISM MANAGEMENT MODEL : A CASE STUDY OF CULTURAL TOURISM DESTINATION “BANMAI ONE-HUNDRED YEARS MARKET” IN CHACHOENGSAO PROVINCE - บุญพร้อมรักษา ศิริรักษ์ (Business Administration and Management Journal Review, 2013)
Sustainable Management of Cultural Tourism Case study of Cultural tourism Ban Mai 100 year Market in Chachoengsao Province. The purpose of this research is to study the behavior and the decision-making process of tourists visiting Ban Mai 100 year market, and current administration system of the market and to propose a plausible management model of sustainable cultural tourism management for Ban Mai 100 year Market. The data collected techniques of this study are questionnaire, interview and observation. The questionnaire which were constructed with 400 Thai tourists who visited the Ban Mai 100 year Market. The researcher conducted interview of 14 managerial team member of the market and the community representatives, and observed several activities of market and managing activities. The study showed that the most visitors were aged 21-30 years old, college students, who earn up to 7,000 baht per month, and the main reasons to visit were for pleasure, leisure and shopping cultural stuff. The study explained that the community aimed to participate and manage its own tourism to be sustainable with the public relation. However, The community should receive some supports from the government and private sectors continuously. In terms of financial management, the market has efficient and effective system, and focuses on stakeholders management. For environmental management, the community has managed waste by their own. However, the basic facilities still need to be developed for sustainable cultural tourism.